Lifestyle intervention in BRCA1/2 mutation carriers: study protocol for a prospective, randomized, controlled clinical feasibility trial (LIBRE-1 study). Issue 1 (December 2016) - Kiechle, Marion; Engel, Christoph; Berling, Anika; Hebestreit, Katrin; Bischoff, Stephan; Dukatz, Ricarda; Gerber, Wolf-Dieter; Siniatchkin, Michael; Pfeifer, Katharina; Grill, Sabine; Yahiaoui-Doktor, Maryam; Kirsch, Ellen; et al.
Abstract Background Women with highly penetrant BRCA mutations have a 55–60% lifetime risk for breast cancer and a 16–59% lifetime risk for ovarian cancer. However, penetrance differs interindividually, indicating that environmental and behavioral factors may modify this risk. These include lifestyle factors such as physical activity status, dietary habits, and body weight. The modification of penetrance by changing lifestyle factors has not thus far been investigated in a randomized trial in BRCA mutation carriers. Methods Therefore, we intend to enroll 60 BRCA1/2 mutation carriers in a pilot feasibility study (Lifestyle Intervention Study in Women with Hereditary Breast and Ovarian Cancer (LIBRE) pilot). This multi-center, prospective, controlled trial aims to randomize (1:1) participants into a (1) multi-factorial lifestyle intervention group (IG) versus (2) the control group with usual care (CG). The primary endpoint is feasibility and acceptance of a structured interdisciplinary lifestyle intervention program over 12 months (at least 70% of the patients to complete the 1-year intervention). Furthermore, the effects on physical fitness, BMI, quality of life, and stress coping capacity will be investigated. During the first 3 months, women in the IG will receive structured, individualized and mainly supervised endurance training of ≥18 MET*h/week (MET = metabolic equivalent task) and personal nutritional counseling based on the Mediterranean diet. During the subsequent 9 months, the IG will receive monthly group training sessions and regular telephone contacts for motivation, whereas the CG will only receive usual care (one general counseling on healthy nutrition and benefits of regular physical activity on health status). At randomization and subsequent time points (3, 6, 12 months), cardiopulmonary fitness will be assessed by spiroergometry and nutritional and psychological status by validated questionnaires. Discussion This pilot study will investigate the optimal strategy to improve physical fitness, nutritional habits, and psychological factors in women at high risk for developing breast or ovarian cancer. The results of this pilot feasibility study will be the basis for a larger prospective randomized trial including clinical events (LIBRE). Trial registration ClinicalTrials.gov, NCT02087592